ANALISIS PENERAPAN IDEAL REDUCING EMISSIONS, DEFORESTATION AND FOREST DEGRADATION DI INDONESIA - Nur Halimah Widowati; Peggy Dian Septi Nur Angraini (Yustitia, 2025)
The implementation of Reducing Emissions, Deforestation, and Forest Degradation in Indonesia still faces many problems. Brazil as one of the first countries to implement Reducing Emissions Deforestation and Forest Degradation has succeeded in reducing deforestation rates from 2005 to 2014. In this paper, the author will compare the implementation of Reducing Emissions, Deforestation, and Forest Degradation in Indonesia and Brazil to find the ideal form of application for Reducing Emissions, Deforestation, and Forest Degradation using doctrinal research methods and using primary also secondary legal materials. The implementation of Reducing Emissions, Deforestation, and Forest Degradation in Indonesia and Brazil still finds various obstacles. The application of the principles of Good Environmental Governance is important in Reducing Emissions Deforestation and Forest Degradation, so the regulation is formed based on sustainable environmental interests, cooperation and coordination between every institutions that take part in forest environmental management and active participation from the community in forming the regulation and the implementation of Reducing Emissions Deforestation and Forest Degradation.